Holding it all together: Family caregivers’ support needs after very early supported discharge post stroke - Karin Törnbom; Gunnel E. Carlsson; Katharina S. Sunnerhagen (PLoS ONE, 2026)
Background Early supported discharge (ESD) facilitates the transition from specialized stroke units to home-based rehabilitation in familiar environments. While ESD has shown positive outcomes for people with stroke, little is known about how their family caregivers experience this transition and the support available once ESD ends. This qualitative study explores the needs, challenges, and expectations of family caregivers during the period following very early supported discharge (VESD) in Sweden. Methods In-depth, individual, semi-structured interviews were conducted with twelve family caregivers of persons who had received VESD after stroke. Data were analysed using thematic analysis with an inductive approach. This design was chosen to capture the caregivers’ rich experiences and to allow themes to emerge directly from the data. Results The findings showed that while the VESD intervention provided important initial support, its limited duration left family caregivers feeling unprepared, anxious, and overwhelmed by their new responsibilities. The overarching themes indicated that caregivers faced emotional strain alongside new and unclear demands. Many struggled to balance caregiving with work and family life, while also coping with relationship changes. The caregivers perceived their role as informal medical coordinators and advocates for the person with stroke within the healthcare system to be particularly challenging. The absence of structured follow-ups, professional guidance, and caregiver-focused support further intensified these challenges. Conclusions This study underscores the need for sustained and comprehensive long-term strategies that include education and mental health support for caregivers in the rehabilitation process after stroke. Moreover, the integration of caregivers into rehabilitation is essential to ensure their preparedness and well-being. Such measures are crucial not only for reducing caregiver burden, but also for promoting better long-term outcomes for both caregivers and the person with stroke.